Critical evaluation and modeling of algal harvesting using dissolved air flotation. Issue 12 (14th July 2014) - Zhang, Xuezhi; Hewson, John C.; Amendola, Pasquale; Reynoso, Monica; Sommerfeld, Milton; Chen, Yongsheng; Hu, Qiang
ABSTRACT In this study, Chlorella zofingiensis harvesting by dissolved air flotation (DAF) was critically evaluated with regard to algal concentration, culture conditions, type and dosage of coagulants, and recycle ratio. Harvesting efficiency increased with coagulant dosage and leveled off at 81%, 86%, 91%, and 87% when chitosan, Al3+, Fe3+, and cetyl trimethylammonium bromide (CTAB) were used at dosages of 70, 180, 250, and 500 mg g−1, respectively. The DAF efficiency‐coagulant dosage relationship changed with algal culture conditions. Evaluation of the influence of the initial algal concentration and recycle ratio revealed that, under conditions typical for algal harvesting, it is possible that the number of bubbles is insufficient. A DAF algal harvesting model was developed to explain this observation by introducing mass‐based floc size distributions and a bubble limitation into the white water blanket model. The model revealed the importance of coagulation to increase floc‐bubble collision and attachment, and the preferential interaction of bubbles with larger flocs, which limited the availability of bubbles to the smaller sized flocs. The harvesting efficiencies predicted by the model agree reasonably with experimental data obtained at different Al3+ dosages, algal concentrations, and recycle ratios. Based on this modeling, critical parameters for efficient algal harvesting were identified. Biotechnol. Bioeng. 2014;111: 2477–2485. © 2014 Wiley Periodicals, Inc.